KEANEKARAGAMAN BELALANG ORDO ORTHOPTERA DI TEPIAN SUNGAI MUSI KOTA PALEMBANG SEBAGAI MATERI KULIAH ENTOMOLOGI DI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS SRIWIJAYA - Riyanto Riyanto (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2017)
Abstract: A research had been done on the order Orthoptera grasshopper diversity on the banks of the Musi River in Palembang. The purpose of this research was to analyze the diversity of the insect order Orthoptera on the banks of the Musi River in Palembang. The location of the study include 100 meters terrestrial area from the banks of the river and the area of ​​the aquatic vegetation was found on the banks of the Musi River in Palembang. The research method was a survey method. The result showed 622 sample of grasshopper, 20 species and 6 families grasshopper in four locations, those are Sungai Ijuk, Gandus, Boombaru and Plaju. Grasshoppers family of the order Orthoptera is Acrididae, Gryllidae, Tetrigidae, Tettigonidae, and Tridactylidae. The highest number of individual grasshopper found in Oxya japonica species, while the lowest number of individuals found in the species of Scudderi sp. The highest number of grasshopper species found in the family Acrididae, while the lowest number of grasshopper species found in the family of Pyrgomorphidae, Tetrigidae, and Tridactylidae. Based on the location of Sungai Ijuk found the highest number of individuals grasshoppers (520), while the lowest number of individuals found in Gandus Grasshoppers (19). The highest diversity index was found in Sungai Ijuk, than Boombaru, Gandus and Plaju. The species diversity index of three areas on the banks of the Musi River in Palembang is medium, while the lower region was Plaju. Plaju had the highestspecies dominance index, while the lowest species dominance index was found in Sungai Ijuk. In that case, in Plaju accord certain species dominance. Boombaru had the highest grasshopper species evenness index, while Plaju had the lowest grasshopper species evenness index. Three sites in this study, those are Boombaru, Gandus and Sungai Ijuk had the highest a high population of evenness index, except Plaju which had small grasshopper species evenness index. The result of the research related toecology material, the classification and morphology of grasshopper. The correlation with ecological materialshowed from habitat conditions. The correlation to the classification of material can be seen from the taxonomic diversity of species in the order Orthoptera. The correlation to the morphology material of insect morphology can be seen from grasshopper. In the process of learning material given to the students of Biology Education Faculty of Teacher Training and Education University of Sriwijaya was a contextual material. Keywords:Diversity, Orthoptera, and Musi River